The Biosaka Efficiency in Supporting Income from Hydroponic Vegetable Cultivation Business - Kumbara Kumbara; Silfia Silfia; Roni Afrizal (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Conventional hydroponics faces nutrient efficiency challenges, impacting profitability and business sustainability. This study is important because it attempts to address these issues through a more economical integration of AB-Mix and Biosaka. This study aims to evaluate the economic efficiency of AB-Mix 37.5% and Biosaka 62.5% compared to the 100% AB-Mix method in hydroponic cultivation. This study uses a case study method at Eco-Hydro, conducted in February–June 2024 in a small hydroponic facility with 400 planting holes. Data were collected through field observations and interviews with 10 hydroponic business actors in Limapuluh Kota Regency. Quantitative analysis includes the calculation of the R/C Ratio and cash flow projections for three years. The results show that the combination of AB-Mix and Biosaka produces an R/C Ratio of 1.4, compared to 1.02 in the 100% AB-Mix method. The net profit per period reached Rp366,219 for the combination of AB-Mix and Biosaka, much higher than Rp24,136 in the 100% AB-Mix method. Cash flow projections show a cumulative income of Rp8,428,896 in three years, confirming the superior economic efficiency of this combination method.